ASSESSMENT FROM THE POINT OF VIEW OF AN INTERVENTION PROGRAM OF THE SOCIO-PERSONAL NEEDS OF DRUGDEPENDENT PEOPLE: THE PERSPECTIVE OF THOSE INVOLVED - Torbay Betancor, Ángela; Cristo Heras, María; Marrero, Mónica (Anales de Psicología / Annals of Psychology, 2003)
The present research sets two objectives. The first one is to know the socio-personal needs of drugdependents who attend reintegration centers, from the users’ point of view and this area professionals’. The second one will evaluate the efficiency of a socio-personal intervention including the previously detected needs. The efficiency of the intervention will be evaluated through change perception and change attribution by the users. The work was carried out on a sample of 81 individuals belonging to three drug-dependence attention centers in Tenerife. The results of the first objective indicate that both users and professionals agree that the socio-personal needs that need working on are, in the first place, the personal area, in the second place, social aspects, and finally, the family area. Only professionals point out the school area as necessary for an intervention. Within the personal area there are more differences between users and professionals when giving priority to the specific needs that need covering. Regarding the second objective, evaluating the intervention according to the users’ perception, the results show that the users value more, both because of the satisfaction and of usefulness, the aspects related to the personal area. Regarding the change attributions, they state that they think they have changed, mainly, because of the contents they worked with, because of the methodology used and because of the kind of affective bond they held with the instructors.